VIRULENCE AND HORIZONTAL TRANSMISSION POTENTIAL OF ENTOMOPATHOGENIC FUNGI AGAINST SUBTERRANEAN TERMITES (Macrotermes gilvus) - Dendu Noutera Pramayuditya Harnieyane; Peristiwati Peristiwati; Any Aryani (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
Indonesia’s tropical climate provides favorable conditions for subterranean termites, particularly Macrotermes gilvus, which cause significant economic losses as wood-destroying pests. Chemical control methods may lead to resistance and environmental problems; therefore, alternative control strategies are needed. This study aimed to evaluate the virulence of Metarhizium sp., Beauveria sp., Aspergillus sp., and Penicillium sp. against M. gilvus based on termite mortality, wood weight loss, and horizontal transmission. Isolates of Metarhizium sp. and Beauveria sp. were obtained from the BSIP Lembang laboratory collection, while Aspergillus sp. and Penicillium sp. were isolated from rhizosphere soil at the same site. The experiment used 13 treatments with three replications, consisting of three conidial concentrations (10⁶, 10⁷, and 10⁸ conidia/ml) and a control. Bioassays were conducted at 26–28 °C and 70–95% relative humidity using no-choice termiticide and horizontal transmission tests. Data were analyzed using the Kruskal–Wallis test. All fungal isolates caused termite mortality and wood weight loss. Beauveria sp. at 10⁸ conidia/ml showed the highest efficacy, achieving 100% mortality within 24 hours. Horizontal transmission was indicated by white hyphal growth on termite bodies. These results demonstrate that entomopathogenic fungi, particularly Beauveria sp., are promising environmentally friendly biological control agents against M. gilvus.